1, 3-Dipolar and Diels–Alder cycloaddition reactions on polyester backbones possessing internal electron-deficient alkyne moieties. Issue 46 (3rd November 2016) - Cetin, Muge; Esen, Cansu; Daglar, Ozgun; Luleburgaz, Serter; Hizal, Gurkan; Durmaz, Hakan; Tunca, Umit
Abstract : A polyester containing electron deficient internal alkyne units derived from acetylene dicarboxylic acid in the main backbone was employed as a polymeric platform in copper free cycloaddition reactions. Abstract : In this study we prepared a series of polyesters containing electron deficient internal alkyne units derived from acetylene dicarboxylic acid in the main backbone. Next, one of the polyesters was employed as a polymeric platform in copper free cycloaddition reactions like, Huisgen type 1, 3-dipolar and Diels–Alder cycloaddition reactions in the presence of various dipoles and dienes, respectively. The 1, 3-dipolar cycloaddition reactions were performed at mild temperatures (rt and 40 °C) in 1, 4-dioxane for 16 h and had moderately high efficiencies (80–100%). However, the Diels–Alder cycloaddition reactions were carried out at higher temperatures (60 to 120 °C) in 1, 4-dioxane for 16 h with reasonable efficiencies (45–97%). Moreover, the polyester was successfully used in one-pot 1, 3-dipolar, sequential 1, 3-dipolar/Diels–Alder, and sequential 1, 3-dipolar cycloaddition/retro-Diels–Alder reactions.